Axial resolution and imaging contrast enhancement in inverted light-sheet microscopy by natural illumination modulation - Wang, Zhi; Qiao, Wei; Jiang, Tao; Chen, Siqi; Lu, Bolin; Ning, Kefu; Jin, Rui; Gong, Hui; Yuan, Jing (Frontiers in Neuroscience, 2022)
Inverted light-sheet microscopy (ILSM) is widely employed for fast large-volume imaging of biological tissue. However, the scattering especially in an uncleared sample, and the divergent propagation of the illumination beam lead to a trade-off between axial resolution and imaging depth. Herein, we propose naturally modulated ILSM (NM-ILSM) as a technique to improve axial resolution while simultaneously maintaining the wide field-of-view (FOV), and enhancing imaging contrast via background suppression. Theoretical derivations, simulations, and experimental imaging demonstrate 15% axial resolution increases, and fivefold greater image contrast compared with conventional ILSM. Therefore, NM-ILSM allows convenient imaging quality improvement for uncleared tissue and could extend the biological application scope of ILSM.